Accuracy of Two Intra-Oral Scanners in Recording the Static Inter-Occlusal Relationship - Bokhary, Abdullah. (Tufts University. Tisch Library., 2021)
Thesis (M.S.)--Tufts University, 2021.; Submitted to the Dept. of Posthodontics.; Advisor: Aikaterini Kostagianni.; Committee: Aikaterini Papathanasiou, Matthew Finkelman, Yo-Wei Chen, and Ala Ali .; Keyword: Dentistry.